Proceedings of the 19th Asia Pacific Automotive Engineering Conference & SAE-China Congress 2017: Selected Papers - (SAE-China), Society of Automotive Engineers; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This Proceedings volume gathers outstanding papers submitted to the 19th Asia Pacific Automotive Engineering Conference & 2017 SAE-China Congress, the majority of which are from China - the largest car-maker as well as most dynamic car market in the world. The book covers a wide range of automotive topics, presenting the latest technical advances and approaches to help technicians solve the practical problems that most affect their daily work.
A Study on a Carmakers Brake Pedal Feel DNA -- Road Noise Prediction Based on FRF-Based Substructuring Method -- A Simple Theory of Fuel Escape from Combustion Room -- Development of a Water Cooled Condenser -- End to End Adaptive Cruise Control Based on Timing Network -- Intelligent Laser Solutions for Automotive Manufacturing.
Keywords: Automotive engineering; Electric power production; Electrical engineering; Automotive Engineering; Electrical Power Engineering; Mechanical Power Engineering; Electrical and Electronic Engineering